On the pivotal role of PPARa in adaptation of the heart to hypoxia and why fat in the diet increases hypoxic injury - Cole, Mark; Abd Jamil, Amira H.; Heather, Lisa C.; Murray, Andrew J.; Sutton, Elizabeth R.; Slingo, Mary; Sebag-Montefiore, Liam; Tan, Suat Cheng; Aksentijević, Dunja; Gildea, Ottilie S.; Stuckey, Daniel J.; Yeoh, Kar Kheng; et al. (Federation of American Society of Experimental Biology, 2016)
The role of peroxisome proliferator activated alpha (PPARα) -mediated metabolic remodeling in cardiac adaptation to hypoxia has yet to be defined. Here, mice were housed in hypoxia for 3 weeks before in vivo contractile function was measured using cine magnetic resonance (MR) imaging. In isolated, perfused hearts, energetics were measured using 31P MR spectroscopy and glycolysis and fatty acid oxidation were measured using 3H labelling. Compared with normoxic, chow-fed control mouse heart, hypoxia decreased PPARα expression, fatty acid oxidation and mitochondrial UCP3 levels, while increasing glycolysis, all of which served to maintain normal ATP concentrations and thereby ejection fractions. A high-fat diet increased cardiac PPARα expression, fatty acid oxidation and UCP3 levels, with decreased glycolysis. Hypoxia was unable to alter the high PPARα expression or reverse the metabolic changes caused by the high fat diet, with the result that ATP concentrations and contractile function decreased significantly. The adaptive metabolic changes caused by hypoxia in control mouse hearts were found to have already occurred in PPARα-/- mouse hearts, and sustained function in hypoxia despite an inability for further metabolic remodelling. We conclude that decreased cardiac PPARα expression is essential for adaptive metabolic remodelling in hypoxia, but is prevented by dietary fat.